2017
DOI: 10.4236/sn.2017.61001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internet Pornography Use and Cyber Infidelity in the Associations between Personality, Attachment, and Couple and Sexual Satisfaction

Abstract: Although adults in romantic relationships currently show more openness to online sexual behaviors [1], these behaviors can nevertheless increase couple conflicts and instability [2]. In the current study, we assess the mediating role of Internet pornography use and cyber infidelity in the relationship between 1) personality and attachment, and 2) couple and sexual satisfaction. A total of 779 participants in couple relationships (average age = 29.9 years) completed a series of online questionnaires. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
1
9
0
3
Order By: Relevance
“…While larger discrepancies were related to lower sexual satisfaction and lower general well-being (lower self-esteem, lower life satisfaction, and increased negative affect), higher SEIM consumption was not directly associated with sexual satisfaction, although the latter remains important in explaining the negative relationship between IASD and general well-being. This lack of connection is rarely reported but has been noted in two studies (Brown, Carroll, et al, 2017; Ferron et al, 2017). These studies shared a similar sample (men in their 30s) and design with this study, as both focused on the associations of SEIM consumption in the context of intimate relationships.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While larger discrepancies were related to lower sexual satisfaction and lower general well-being (lower self-esteem, lower life satisfaction, and increased negative affect), higher SEIM consumption was not directly associated with sexual satisfaction, although the latter remains important in explaining the negative relationship between IASD and general well-being. This lack of connection is rarely reported but has been noted in two studies (Brown, Carroll, et al, 2017; Ferron et al, 2017). These studies shared a similar sample (men in their 30s) and design with this study, as both focused on the associations of SEIM consumption in the context of intimate relationships.…”
Section: Discussionmentioning
confidence: 87%
“…Sexually explicit Internet material (SEIM), also known as online pornography, has been widely consumed by individuals for purposes including solitary sexual pleasure (Morgan, 2011; Brown, Durtschi, et al, 2017), attempts to enhance sexual communication (Kohut et al, 2017), and to assess the quality of their sex lives (Cooper et al, 1999; Wright et al, 2018). The rise in popularity of SEIM has prompted researchers to examine its impact on sexual and relational well-being (Ferron et al, 2017; Szymanski & Stewart-Richardson, 2014; Willoughby et al, 2016). Scholars have become increasingly interested in understanding why and how such consumption influences users (Štulhofer et al, 2007; Wright, Sun, et al, 2019).…”
mentioning
confidence: 99%
“…As another example, Gwinn, Lambert, Fincham, and Maner (2013) found that earlier pornography consumption was associated with later extradyadic sexual activity among a sample of male and female college students in the United States. As another example, Ferron, Lussier, Sabourin, and Brassard (2017) surveyed Canadian men and women and found that the use of pornography was correlated with having engaged in cybersex outside of their committed relationship. As another example, Daneback, Traeen, and Mansson (2009) found that pornography consumption was associated with having had extradyadic sexual encounters in their survey of Norwegian men and women.…”
Section: Mediationmentioning
confidence: 99%
“…Willoughby et al (2014) controlled for demographic (e.g., age, ethnicity) and personality (e.g., impulsivity) factors in their study of pornography use and sexual partners but did not control for sexual attitudes. Ferron et al (2017) adjusted for attachment-styles (avoidance, anxiety) in their study of pornography consumption and cyberinfidelity but did not adjust for sexual attitudes. Mahapatra and Saggurti (2014) controlled for sociodemographic (e.g., education, age) factors in their study of pornography use and extramarital sex but did not consider the potential confounding role of sexual attitudes.…”
Section: Confoundingmentioning
confidence: 99%
“…Studies by Abdi, Khoshkonesh, Porebrahim & Mohammadi (2012) and McDaniel et al (2017) state that unfaithful partners have an avoidant or anxious attachment rather than a secure one. Ferron, Lussier, Sabourin & Brassard (2016) explain how activation of the attachment system is associated with the desire for emotional and sexual experiences in the online environment, which satisfy the need for love that anxious individuals have.…”
Section: Introductionmentioning
confidence: 99%